Enrichment of HDL proteome and phospholipidome from human serum via IMAC/MOAC affinity. (11th September 2019) - Javeed, Rabia; Hussain, Dilshad; Jabeen, Fahmida; Saeed, Adeela; Fatima, Batool; Ashiq, Muhammad Naeem; Najam‐ul‐Haq, Muhammad
Abstract: High‐density lipoproteins (HDLs) have anti‐inflammatory and antioxidant properties and are potentially cardio‐protective. Defective HDL function is caused by alterations in both the proteome and lipidome of HDL particles. As potential biomarkers, the development of analytical methods is necessary for the enrichment of HDLs. Therefore, a method for selective enrichment of HDLs using immobilized metal ion affinity chromatography (IMAC) and metal oxide affinity chromatography (MOAC) is presented. SPE‐based isolation of HDLs from whole serum is adopted as an alternative to traditional ultracentrifugation methods followed by SDS–PAGE. The enrichment mechanism relies on isoelectric points of lipoproteins and metal oxide. Negatively charged lipoprotein particles interact with positively charged metal oxides and IMAC affinity, which acts as a cation. Identified proteins from HDL through MALDI–MS analysis are apo AI, AII, AIV, CI, CIII, E, J, M, H, serum amyloid A and other nonapoproteins that are part of HDL particles and perform cellular functions. This serum‐based proteomics approach gives insight into the functional role of HDL. HDL‐associated phospholipids have also been analyzed by LDI–MS. Results suggest that the adopted analytical strategy is a feasible idea to extract lipoproteins from serum. A comparative study of healthy and diseased samples using this approach will provide valuable information in future.